Genetic Algorithm Optimization Design of Gradient Conformal Chiral Metamaterials and 3D Printing Verification for Morphing Wings - Qian Zheng; Weijun Zhu; Quan Zhi; Henglun Sun; Dongsheng Li; Xilun Ding (Chinese Journal of Mechanical Engineering, 2024)
Abstract This paper proposes a gradient conformal design technique to modify the multi-directional stiffness characteristics of 3D printed chiral metamaterials, using various airfoil shapes. The method ensures the integrity of chiral cell nodal circles while improving load transmission efficiency and enhancing manufacturing precision for 3D printing applications. A parametric design framework, integrating finite element analysis and optimization modules, is developed to enhance the wing’s multidirectional stiffness. The optimization process demonstrates that the distribution of chiral structural ligaments and nodal circles significantly affects wing deformation. The stiffness gradient optimization results reveal a variation of over 78% in tail stiffness performance between the best and worst parameter combinations. Experimental outcomes suggest that this strategy can develop metamaterials with enhanced deformability, offering a promising approach for designing morphing wings.